2022
DOI: 10.1155/2022/9127539
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Risk Management of Sports Venues and Olympic Sports Cooperation Spirit under Complex Environment

Abstract: The understanding of sports event risk and Olympic sports cooperation spirit, as well as the systematic analysis and research of sports event risk management, are still in their early stages in China’s sports theory circle. Institutions for developing sports talent also disregard programmes designed to increase the risk awareness and Olympic spirit of sports workers. This essay provides an overview of the concepts of sports event risk and Olympic sports cooperation spirit based on reality. This paper examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Current research on sports venues has seen scholars exploring the topic from various angles. From a sociological perspective, topics include: terrorist attacks on sports venues 9 , naming patterns of these venues 10 , risks associated with sporting events held within them, the spirit of Olympic sports collaboration, and systematic risk management 11 . Economically, scholars have documented financing methods for sports venues 12 and delved into audience-perceived risks, price perceptions, and continued consumption intentions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Current research on sports venues has seen scholars exploring the topic from various angles. From a sociological perspective, topics include: terrorist attacks on sports venues 9 , naming patterns of these venues 10 , risks associated with sporting events held within them, the spirit of Olympic sports collaboration, and systematic risk management 11 . Economically, scholars have documented financing methods for sports venues 12 and delved into audience-perceived risks, price perceptions, and continued consumption intentions 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%